PERBANDINGAN PEMBERIAN METODE TEPID WATER SPONGE DENGAN PLESTER KOMPRES DEMAM TERHADAP PENURUNAN SUHU TUBUH PASIEN ANAK - Anita Dwi Ariyani; Nurary Alief Theria; Anang Satrianto; Fany Anitarini (PROFESSIONAL HEALTH JOURNAL, 2024)
Most fevers in children are the result of changes in the heat center (thermoregulation) in the hypothalamus. Fever can be treated pharmacologicially and non-pharmacologically. There are various non-pharmacological therapies, one of which is using tepid water sponge therapy and fever compress plaster fever. The purpose of this study was to compare the effectiveness of the tepid water sponge on decreasing body temperature, the effectinevess of the fever compress plaster on reducing body temperature and the effectiveness of the tepid water sponge with fever compress plaster on reducing body temperature. The design of this study used a two-group pretest-posttest design aproach, the number of samples was 20 respondents which were divided into10 respondents in the tepid water sponge group and 10 respondents in the fever compress plaster group using the accidental sampling method. Data analysis in this study used paired sample t-test with observation sheet measuring instrument. The result showed a decrease in the average temperature of 0,7°C in the tepid water sponge group and 0,1°C in the fever compress plester group. For the result of analysis in the tepid water sponge group the ƿ value was 0,000 and the t count was 12,124. The fever compress plaster group got ƿ value 0,037 and t count 2, 449. Which means that there was a difference in the decrease in body temperature after the tepid water sponge and compress plaster with a p-value <0.05. Tepid water sponge is more effective in lowering body temperature compared to compress plaster.